Best practice in the diagnosis and treatment of varicocele in children and adolescents. Issue 9 (September 2018) - Macey, Matthew R.; Owen, Ryan C.; Ross, Sherry S.; Coward, R. Matthew
A varicocele is an abnormal dilation of the pampiniform plexus of veins in the scrotum which begins at puberty in approximately 15% of males. Although common in the general population and often asymptomatic, varicoceles are associated with gonadal dysfunction including testicular atrophy, infertility, and hypogonadism in a subset of men diagnosed later in life. Because of the high prevalence and uncertain pathogenesis, definitive management guidelines for varicoceles diagnosed in the pediatric and adolescent population remain poorly defined. The varicocele is the most common etiology of male factor infertility, and treatment in the pediatric and adolescent population may improve semen quality and improve fecundity in adulthood. Evaluation of the pediatric and adolescent varicocele should include history, physical exam, and measurement of testicular volume with orchidometer or ultrasound. Testicular volume differentials and peak retrograde flow on Doppler ultrasonography are important factors in risk stratification of the pediatric varicocele population. Semen analysis and reproductive endocrine assessment should also be considered as part of the workup for adolescent patients. A variety of treatment approaches exist for varicocele, and while the microsurgical subinguinal approach is the gold standard for the adult population, it has yet to be confirmed as superior for the adolescent population. Referral to an andrologist for the adolescent patient with varicocele should be considered in equivocal cases. While active treatment of varicocele in the pediatric and adolescent population is controversial, it is clear that some untreated patients will suffer symptoms later in life, while overtreatment remains a concern for this large, vulnerable population. Therefore, surveillance strategies and improved accuracy in diagnosis of clinically important pediatric varicoceles prompting treatment are needed in the future.